PERLINDUNGAN HUKUM TERHADAP KORBAN PELECEHAN SEKSUAL - Putri Widia Ningsih; Gadis Prasiska Sembiring, Reh Bungana Beru Perangin-angin, Maulana Ibrahim (INTELIGENSIA MEDIA, 2023)
Sexual harassment is an act that is detrimental and damages a person's dignity, and can occur in various places and situations, whether in the family, workplace or in public places. Legal protection for victims of sexual harassment is very important to maintain the security and welfare of society. This research aims to determine the legal protection provided to victims of sexual harassment in Indonesia. The research method used is normative legal research with a statutory approach and a conceptual approach. The research results show that legal protection for victims of sexual harassment is regulated in Article 5 and Article 6 of Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims. Apart from that, the establishment of victim protection institutions and increasing legal sanctions are also effective ways to provide legal protection for victims of sexual harassment.